“His Comedie unto his Theatre”: Genre in the Early Modern Dramatic Epilogue - Emily Smith (Sillages Critiques)
This article suggests that the multifaceted concept of “genre” is a fruitful tool with which to examine the complex conventions of early modern dramatic epilogues. With the ability to reflect upon the play which they conclude whilst also looking forward to its reception, epilogues of this period enjoy – and provide – a unique vantage point. By employing corpus analysis, this paper examines how epilogues create a formal genre in themselves, yet also contribute to the conceptualisation of genre in plays more broadly. It concludes that epilogues are deeply intertextual in two senses: as a discrete genre in themselves, and as commentators on specific works.